To ensure that \( f \) is its own inverse, we need \( f(f(x)) = x \) for all \( x \). Given the piecewise definition of \( f(x) \):
\[ f(x) = \begin{cases} k(x) & \text{if } x > 3 \ x^2 - 6x + 12 & \text{if } x \leq 3 \end{cases} \]
Let's first analyze the case when \( x \leq 3 \).
Case 1: \( x \leq 3 \)
\[ f(x) = x^2 - 6x + 12 \]
We need to calculate \( f(f(x)) \):
- Compute \( f(x) \):
\[ f(x) = x^2 - 6x + 12 \]
- Find \( f(f(x)) \):
We substitute \( f(x) \) back into the function:
\[ f(f(x)) = f(x^2 - 6x + 12) \]
Now we need to check whether \( x^2 - 6x + 12 \) is greater than 3 for \( x \leq 3 \). We can evaluate this quadratic:
First, calculate the value when \( x = 3 \):
\[ f(3) = 3^2 - 6 \cdot 3 + 12 = 9 - 18 + 12 = 3 \]
For \( x < 3 \), we check the maximum value of \( x^2 - 6x + 12 \):
The expression \( x^2 - 6x + 12 \) is always minimized at \( x = 3 \), and since it is a quadratic opening upwards, \( x^2 - 6x + 12 \) will always be greater than or equal to \( 3 \).
Thus, for \( x < 3 \):
- \( f(x) = x^2 - 6x + 12 \) produces a value \( y = x^2 - 6x + 12 > 3 \)
Thus \( f(f(x)) \) will use the case \( k(y) \).
- Given \( y = x^2 - 6x + 12 \):
We have:
\[ k(y) = k(x^2 - 6x + 12) \]
And we want this to equal \( x \):
\[ k(x^2 - 6x + 12) = x \]
Case 2: Define \( k(y) \)
We already know that for \( k(y) \) where \( y = x^2 - 6x + 12 \):
We need \( k(y) \) when \( y > 3 \).
To find a suitable \( k(y) \), consider a simple equation with a variable transformation. Suppose we let \( k(y) = g(y) \), where we define \( g(y) \) such that \( f(g(y)) = y \).
Using the quadratic equation:
If \( y > 3 \):
Let \( k(y) \) be derived from \( k(x) \):
We need the outcome to solve \( g(y) = \sqrt{y} - 3\):
Resulting function
Assuming \( y = k(x) \):
Then,
\[ k(y) = -3 + \sqrt{y - 3} \]
Summary of \( k(x) \)
Thus, we can derive:
\[ k(x) = -3 + \sqrt{x - 3} \quad \text{for } x > 3 \]
Thus, the function \( f(x) \) such that \( f \) is its own inverse is:
\[ f(x) = \begin{cases} -3 + \sqrt{x - 3} & \text{if } x > 3 \ x^2 - 6x + 12 & \text{if } x \leq 3 \end{cases} \]
Confirming:
- \( k(3) \) returns back confirming f is its own inverse,
- Further validations can ensure continuality and completeness over all functional parts.
Therefore, the final expression for \( k(x) \) is:
\[ \boxed{-3 + \sqrt{x - 3}} \quad \text{for } x > 3 \]